Southeast Asia: Beyond Borders and Boundaries, eds. Samuel C.Y. Ku and Herlin Chien - Azmil Tayeb (Kajian Malaysia, 2019)
The region Southeast Asia as a subject of academic inquiry has long fascinated scholars who are interested in its strategic location that straddles the two great civilisations of China and India. Colonialism, especially since the 19th century, effectively carved and moulded the region into its current form with all its commonalities and cleavages (Reid 1988; Lieberman 2003). In the mid-20th century Southeast Asia assumed a special importance for policymakers as the region became deeply embroiled in the Cold War, manifested by the Vietnam War and numerous communist insurgencies. Centres for Southeast Asian Studies were established in various prominent universities in the USA, UK, and Australia, in order to study and understand the region in a deep, systematic, and transdisciplinary manner. Since the end of Cold War in 1991 academic interest in Southeast Asia has gradually dwindled as the focus shifts to the conflict-ridden Middle East and the rising might of China. Southeast Asia as an area study is in need of re-evaluation and its importance to theory-making must be emphasised so as to stave off irrelevancy (Chou and Houben 2006; Sears 2007; Kuhonta, Slater and Vu 2008). The book Southeast Asia: Beyond Borders and Boundaries, edited by Samuel C.Y. Ku and Herlin Chien operates in similar vein as it looks at the region through its fluid interconnectivity that transcends national boundaries but also hamstrung by domestic interests and institutional paralysis of ASEAN, and how this dynamic is shaped by socio-economic-political forces from within and without, chief among which is the looming spectre of its omnipotent next-door neighbour China.